1990
DOI: 10.21273/hortsci.25.7.764
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photoperiod on Liatris spicata Generative Shoot Growth

Abstract: One-year-old corms of Liatris spicata Willd. produced from seed and 2-year-old corms from division of previously forced corms were placed under 8 hours of natural daylight plus 0, 4, 6, or 8 hours of incandescent (5 μmol·s-l·m-2) day continuation to equal 8-, 12-, or 16-hour photoperiods. Plants were grown under these photoperiods during the first 35 days after shoot emergence (initial) and then were grown under a second photoperiod o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Liatris spicata (L.) Willd. produced the highest yields of long-stemmed cut flowers when an initial 35d SD treatment was followed by LD (Espinosa and Healy, 1990). Iversen and Weiler (1994) showed that L. clethroides does not flower in SD, and subsequent studies on growth and flowering of this crop in response to cooling were conducted under LD conditions (Lewis et al, 1999).…”
mentioning
confidence: 99%
“…Liatris spicata (L.) Willd. produced the highest yields of long-stemmed cut flowers when an initial 35d SD treatment was followed by LD (Espinosa and Healy, 1990). Iversen and Weiler (1994) showed that L. clethroides does not flower in SD, and subsequent studies on growth and flowering of this crop in response to cooling were conducted under LD conditions (Lewis et al, 1999).…”
mentioning
confidence: 99%
“…1), stem elongation ( Fig. 3) (Espinosa and Healy, 1990), and floral initiation in Liatris are independent events with specific environmental control mechanisms. Kofranek (1980) reported that 70 days from planting to flowering were required when corms were planted between spring and autumn, with winter plantings requiring longer to flower.…”
Section: Discussionmentioning
confidence: 98%
“…Although a NI plays an important role in obtaining long, flowering shoots, temperature strongly interacted with photoperiod to promote stem elongation. Previous photoperiod studies (Espinosa and Healy, 1990;Grower Books, 1980;Mevel, 1983;Zieslin, 1985;Zieslin and Geller, 1983b) were conducted at only one temperature, therefore calling into question the exact effect of photoperiod on stem elongation.…”
Section: Discussionmentioning
confidence: 99%